2018
DOI: 10.1002/ajmg.a.40469
|View full text |Cite
|
Sign up to set email alerts
|

Risk of hepatic neoplasms in Wolf–Hirschhorn syndrome (4p‐): Four new cases and review of the literature

Abstract: Wolf–Hirschhorn syndrome (WHS) is a rare contiguous gene deletion disorder characterized by distinctive craniofacial features, prenatal/postnatal growth deficiency, intellectual disability, and seizures. Various malformations of internal organs are also seen. Neoplasia has not been documented as a typical feature of WHS. We review the three prior reports of hepatic neoplasia in WHS and add four previously unreported individuals. We propose that, in the context of the rarity of WHS, these seven cases suggest th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
0
11
0
1
Order By: Relevance
“…Only 11 adults with WHS have been reported so far, with age range between 19 and 37 years (Battaglia et al, 2018; Coppola et al, 2013; Lopes et al, 2005; Ogle et al, 1996; Opitz, 1995; Prunotto et al, 2013; Smith et al, 1995). Eight of 11 were said to have health problems, such as, severe thoracic or thoracolumbar scoliosis, acute pancreatitis, hepatitis, gallstones, diabetes (developed at age 22 years in one), and chronic renal failure following bilateral renal hypoplasia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only 11 adults with WHS have been reported so far, with age range between 19 and 37 years (Battaglia et al, 2018; Coppola et al, 2013; Lopes et al, 2005; Ogle et al, 1996; Opitz, 1995; Prunotto et al, 2013; Smith et al, 1995). Eight of 11 were said to have health problems, such as, severe thoracic or thoracolumbar scoliosis, acute pancreatitis, hepatitis, gallstones, diabetes (developed at age 22 years in one), and chronic renal failure following bilateral renal hypoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Prunotto et al (2013) reported on two adult WHS patients in whom hepatic adenomas were detected at age 20 and 11 years, respectively. More recently, Battaglia et al (2018) documented four previously undescribed individuals with WHS who developed hepatic neoplasia between ages 15 and 32. Therefore, we are planning to study as many adults with WHS as we can recruit, in order to obtain the most accurate natural history information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumors have been reported in several WHS cases (4952). In particular, the discovery of neuroblastoma in a child with WHS implicated the association of these two phenotypes (51).…”
Section: New Insights Into Tumorigenesismentioning
confidence: 99%
“…), обусловливающих имеющийся у ребенка клинический симптомокомплекс. Учитывая постоянное продолжающееся внешнее и внутреннее радиационное облучение в связи с проживанием в зоне радиацион-ного загрязнения, нельзя в дальнейшем исключить высокий риск развития злокачественных новообразований у ребенка [7].…”
unclassified